PERBEDAAN HASIL BELAJAR MATEMATIKA SISWA YANG DIAJAR DENGAN MODEL PEMBELAJARAN ELABORASI DAN MODEL PEMBELAJARAN TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DI KELAS IX MTS AMALIYAH TANJUNG TIGA PADA MATERI PRISMA DAN LIMAS TA. 2016/2017 - Fibri Rakhmawati (State Islamic University of North Sumatra, 2017)
The aim of this research is to know the difference of learning result of student's mathematics with learning model of elaboration and model of learning type Student Teams Achievement Division (STAD). This research is quantitative research, with research type quasi experiment. The population is all students of IX class MTs Amaliyah Tanjung Tiga Academic Year 2016/2017 the number of the students 140 . The sample in this study were 30 students in the class IX-A and 30 students in the class IX-B. Data analysis was doing by variance analysis (ANAVA). Result finding showed : 1) the amount results of learning of student mathematicstaught by using elaboration learning model with an average value of 70.17 and has a variance value of 216.28. 2) the amount results of learning of student mathematicstaught by Student Teams Achievemnt Division (STAD) learning model with an average score of 60.33 and a variance value of 158.92. 3) there are differences of students' mathematics learning result taught with elaboration learning model and learning model of type Student Teams Achievement Division (STAD) with Fcount> F(table) that is equal to F(count) = 5,936 and Ftable = 4,007. The conclusion of this research showed that the result of learning of student mathematics taught by using elaboration learning model is better than using model of learning type Student Teams Achievement Division (STAD).